Measuring the Microscopic Structures of Human Dental Enamel Can Predict Caries Experience - Kelly, Ariana M; Kallistova, Anna; Küchler, Erika C; Romanos, Helena F; Lips, Andrea; Costa, Marcelo C; Modesto, Adriana; Vieira, Alexandre R (Journal of personalized medicine, 2020)
OBJECTIVES: The hierarchical structure of enamel gives insight on the properties of enamel and can influence its strength and ultimately caries experience. Currently, past caries experience is quantified using the decayed, missing, filled teeth/decayed, missing, filled surface (DMFT/DMFS for permanent teeth; dmft/dmfs for primary teeth), or international caries detection and assessment system (ICDAS) scores. By analyzing the structure of enamel, a new measurement can be utilized clinically to predict susceptibility to future caries experience based on a patient's individual's biomarkers. The purpose of this study was to test the hypothesis that number of prisms by square millimeter in enamel and average gap distance between prisms and interprismatic areas, influence caries experience through genetic variation of the genes involved in enamel formation. MATERIALS AND METHODS: Scanning electron microscopy (SEM) images of enamel from primary teeth were used to measure (i) number of prisms by square millimeter and interprismatic spaces, (ii) prism density, and (iii) gap distances between prisms in the enamel samples. The measurements were tested to explore a genetic association with variants of selected genes and correlations with caries experience based on the individual's DMFT+ dmft score and enamel microhardness at baseline, after an artificial lesion was created and after the artificial lesion was treated with fluoride. RESULTS: Associations were found between variants of genes including ameloblastin, amelogenin, enamelin, tuftelin, tuftelin interactive protein 11, beta defensin 1, matrix metallopeptidase 20 and enamel structure variables measured (number of prisms by square millimeter in enamel and average gap distance between prisms and interprismatic areas). Significant correlations were found between caries experience and microhardness and enamel structure. Negative correlations were found between number of prisms by square millimeter and high caries experience (r value= -0.71), gap distance between prisms and the enamel microhardness after an artificial lesion was created (r value= -0.70), and gap distance between prisms and the enamel microhardness after an artificial lesion was created and then treated with fluoride (r value= -0.81). There was a positive correlation between number of prisms by square millimeter and prism density of the enamel (r value = 0.82). CONCLUSIONS: Our data support that genetic variation may impact enamel formation, and therefore influence susceptibility to dental caries and future caries experience. CLINICAL RELEVANCE: The evaluation of enamel structure that may impact caries experience allows for hypothesizing that the identification of individuals at higher risk for dental caries and implementation of personalized preventative treatments may one day become a reality.